Survival outcome and prognostic factors in patients with chemotherapy-naive metastatic castration-resistant prostate cancer treated with abiraterone acetate – real-world experience in Vietnam - Do, Tu Anh; Nguyen, Thai Hoa Thi; Nguyen, Hau Xuan; Nguyen, Loi Dinh; Nguyen, Chu Van (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. In real life, metastatic castration-resistant prostate cancer patients (mCRPC) had more complex clinical presentation than patients in the COU-AA-302 trial. This study primarily aimed to describe the overall survival of chemotherapy-naive mCRPC treated with abiraterone acetate plus prednisone (AAP). Other relevant outcomes and baseline characteristics of these patients were also evaluated. Material and methods. This retrospective, observational study collected data from chemotherapy-naive mCRPC patients treated with AAP in Vietnam. Kaplan-Meier curves were used to estimate time to treatment failure (TTF), and overall survival (OS). The impact of baseline characteristics on OS was explored using univariate and multivariate Cox proportional hazard models. Results. Data from 65 eligible patients were analyzed. The rate of PSA response was 73.8%, median PSA PFS was 10.5 months (95% CI: 7.4–13.6), median TTF was 15 months (95% CI: 11.1–18.9), and median OS was 24.9 months (95% CI: 18.9–30.9). Shorter OS was significantly associated with a higher Gleason score (≥8), shorter time from ADT start to mCRPC (<12 months), visceral metastases, and <50% PSA decline (p<0.05). Conclusion. Abiraterone acetate plus prednisone is well tolerated and effective for chemotherapy-naive mCRPC patients in clinical practice. Moreover, Gleason score, visceral metastasis, time from ADT start to mCRPC, and PSA response are the independent indicators for predicting the OS of mCRPC patients in both univariate and multivariate analyses.
All objects of the protocol’s this study was approved by the Science and Ethical Committee of Hanoi Medical University, Vietnam as number: 6811/QD-DHYHN.
Keywords: abiraterone acetate; metastatic castration-resistant prostate cancer; overall survival; real-world evidence